Pemanfaatan Media Sosial Tiktok Sebagai Media Komunikasi Pemasaran Pada Akun @Bioaquaofficialstore - Khumaero, Latifatul; Fournawati, Sri Murdilah; Alamsyah, Alamsyah (Social Science Academic, 2023)
The skincare business in Indonesia is indeed quite promising, now Indonesian people care more about the health and beauty of their skin. Bioaqua Official is a Skin Care product that provides solutions to Indonesian people's skin problems. Bioaqua Official is a skincare product that has been around since 2019. They use TikTok social media as a marketing communication medium so they can continue to compete with other products. Remembering that TikTok is a social media that now has a lot of users in Indonesia. This research aims to find out how Bioaqua Official uses Tiktok social media as a marketing communication medium on the @Bioaquaofficialstore account. This research uses a descriptive qualitative research method where the data obtained is the result of observation, interviews and documentation. The research results show that Bioaqua Official is able to make good use of Tiktok social media as a marketing communication medium, successfully selling millions of products and having millions of followers on Tiktok.